O corpus dos mosaicos romanos em Portugal - Abraços, Maria de Fátima (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
This article is a reflection about the publication of an international and national corpus of roman mosaics realised until today, the importance of the corpus towards the academic studies of roman mosaics in Portuguese territory and the publication of future volumes of this corpus.